Consideration of the haplotype diversity at nonallelic homologous recombination hotspots improves the precision of rearrangement breakpoint identification. Issue 12 (22nd September 2017) - Hillmer, Morten; Summerer, Anna; Mautner, Victor‐Felix; Högel, Josef; Cooper, David N.; Kehrer‐Sawatzki, Hildegard
Abstract: Precise characterization of nonallelic homologous recombination (NAHR) breakpoints is key to identifying those features that influence NAHR frequency. Until now, analysis of NAHR‐mediated rearrangements has generally been performed by comparison of the breakpoint‐spanning sequences with the human genome reference sequence. We show here that the haplotype diversity of NAHR hotspots may interfere with breakpoint‐mapping. We studied the transmitting parents of individuals with germline type‐1 NF1 deletions mediated by NAHR within the paralogous recombination site 1 (PRS1) or paralogous recombination site 2 (PRS2) hotspots. Several parental wild‐type PRS1 and PRS2 haplotypes were identified that exhibited considerable sequence differences with respect to the reference sequence, which also affected the number of predicted PRDM9‐binding sites. Sequence comparisons between the parental wild‐type PRS1 or PRS2 haplotypes and the deletion breakpoint‐spanning sequences from the patients (method #2) turned out to be an accurate means to assign NF1 deletion breakpoints and proved superior to crude reference sequence comparisons that neglect to consider haplotype diversity (method #1). The mean length of the deletion breakpoint regions assigned by method #2 was 269‐bp in contrast to 502‐bp by method #1. Our findings imply that paralog‐specific haplotype diversity of NAHR hotspots (such as PRS2) and population‐specific haplotype diversity must be taken into account in order to accurately ascertain NAHR‐mediated rearrangement breakpoints. Abstract : Characterization of paralog‐specific haplotype diversity as well as population‐specific haplotype diversity of NAHR hotspots is necessary in order to accurately ascertain NAHR‐mediated rearrangement breakpoints. This is concluded from our observation that in the transmitting parents of 25 individuals with germline type‐1 NF1 microdeletions mediated by NAHR within the PRS1 or PRS2 NAHR hotspots, considerable parental PRS1 or PRS2 haplotype diversity was identified, which also affected the number of predicted PRDM9‐binding sites.